2015
DOI: 10.1007/s40653-015-0058-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Absence and Reintegration of a Prisoner of War Father from the Perspective of His Children as Adults

Abstract: The studied test case presents the adult voices of Israeli children whose fathers were prisoners of war (POWs) in Egypt from 1969 to 1973. The study's findings indicate long-term effects of the captivity on the children of POWs, and that an inner formative experience associated with the period of the father's absence remains despite his return. The findings are explained by means of ambiguous loss theories and by loss and bereavement theories. Recommendations emerge for ambiguous loss to be recognized as a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Thus, while only a relatively small proportion of people may present with the syndrome of depression, many may experience one or more symptoms. This is evidenced by consistent reports in the qualitative literature of symptoms typically associated with depression, including feelings of intense sadness (DeYoung & Buzzi, 2003;Luster, Qin, Bates, Johnson, & Rana, 2008;Luster, Qin, Bates, Johnson, & Rana, 2009;Robins, 2010a;Berthoud & Bickel-Nikles, 2013), sorrow, despair, emotional pain, numbness (Hollander, 2016), and the sensation of living in a "black cloud" (Ben-Asher & Shalev, 2015).…”
Section: Psychological Responses To Disappearance Due To Forced Cirsupporting
confidence: 55%
See 1 more Smart Citation
“…Thus, while only a relatively small proportion of people may present with the syndrome of depression, many may experience one or more symptoms. This is evidenced by consistent reports in the qualitative literature of symptoms typically associated with depression, including feelings of intense sadness (DeYoung & Buzzi, 2003;Luster, Qin, Bates, Johnson, & Rana, 2008;Luster, Qin, Bates, Johnson, & Rana, 2009;Robins, 2010a;Berthoud & Bickel-Nikles, 2013), sorrow, despair, emotional pain, numbness (Hollander, 2016), and the sensation of living in a "black cloud" (Ben-Asher & Shalev, 2015).…”
Section: Psychological Responses To Disappearance Due To Forced Cirsupporting
confidence: 55%
“…In particular, sudden feelings of anxiety (ICRC, 2009;Robins, 2010b), panic attacks (Berthoud & Bickel-Nikles, 2013), constant worry about the missing person, (Luster et al, 2008(Luster et al, , 2009, and a preoccupation with thoughts related to the loss (Campbell & Demi, 2000;Hollander, 2016;Munczek & Tuber, 1998;Robins, 2010a). Two studies described how, among children with missing fathers, anxiety was often reflected in attention and concentration difficulties (Ben-Asher & Shalev, 2015;Quirk & Casco, 1994). Several studies identified anxiety as having manifested into psychosomatic symptoms, including constant physical sickness (Robins, 2010a), chronic chest and/or stomach pain (ICRC, 2009;Robins, 2010b), heart palpitations, headaches (Quirk & Casco, 1994), and exacerbation of pre-existing health problems (Berthoud & Bickel-Nikles, 2013).…”
Section: Psychological Responses To Disappearance Due To Forced Cirmentioning
confidence: 99%